Faktor yang Mempengaruhi Keputusan Pembelian Skeptics - Aang Syahdina; M. Fazar Rizky; Diandra Putri Sintara; Divi Fatihah Bilkis; Zakia Sabania (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to test how the influence of brand identity, price, and Product Quality on Brand Choice for Skeptics items. Essential information was utilized in this consider, collected through convenience inspecting over a ten-day period utilizing Google Shapes from 100 shoppers of Skeptics items on Tokopedia. Information investigation strategies included the external demonstrate, internal demonstrate, and speculation testing. The oddity of this investigate lies within the utilize of the SEM Keen PLS 4.0 application, as restricted to past considers which utilized SPSS. Hypothesis testing comes about show that brand identity contrarily influences the Buy Choice for Skeptics products, Product Quality emphatically impacts the Buy Decision, and Price too incorporates a positive affect on the Buy Choice. The consider recommends that proprietors ought to alter their branding techniques to upgrade brand acknowledgment, develop a more positive notoriety, and cultivate passionate engagement with customers to more successfully impact buy choices in a competitive advertise. The dominant variable for purchasing decision about skeptical produk is product quality,which is 0.154.